Å snakke med de døde. En studie i Ingvar Ambjørnsens novelle Skallene - Andersen, Bjørn Inge Berger; Heldal, Anja; Johnsen, Henry Andreas Øien; Nordøy, Atle Tord; Velsand, Birgit (Nordlit, 2006)
Ingvar Ambjørnsen’s short stories are often described as dark, depicting a meaningless universe. Our analysis of his short story “Skallene” from the collection Sorte Mor (1994) shows that this description is not necessarily pertinent. We argue that the story’s meaning relies upon hidden intertextual references, eastern philosophy and complex life worlds. We conclude that the immediate impression of meaninglessness is in fact contradicted by the deeper structures of the text itself.
Keywords: Ingvar Ambjørnsen; Skallene; short story; life worlds; ethos; intertextuality; palimpsest; Eastern philosophy/religion